2016
DOI: 10.1016/j.envpol.2016.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and toxicological characterisation of anticancer drugs in hospital and municipal wastewaters from Slovenia and Spain

Abstract: Anticancer drugs are continuously released into hospital and urban wastewaters, where they, most commonly, undergo conventional treatment in wastewater treatment plants (WWTPs). Wastewaters contain complex mixtures of substances including parent compounds, their metabolites and transformation products (TPs). In this study, samples of hospital effluents and WWTP influents and effluents from Slovenia and Spain were analyzed for twenty-two selected anticancer drugs, their metabolites and transformation products. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(60 citation statements)
references
References 53 publications
(63 reference statements)
1
58
0
1
Order By: Relevance
“…It has been reported that almost all the anticancer drugs are toxic to crustacean Ceriodaphnia dubia in chronic toxicity studies. Similar results have been demonstrated in the Zebra fish where comet assay showed fragmentation of DNA [14]. In all, there is requirement of research in this area especially when a "mixture" of anticancer drugs are present in a water body.…”
Section: Anticancer Drugs Toxicitysupporting
confidence: 79%
“…It has been reported that almost all the anticancer drugs are toxic to crustacean Ceriodaphnia dubia in chronic toxicity studies. Similar results have been demonstrated in the Zebra fish where comet assay showed fragmentation of DNA [14]. In all, there is requirement of research in this area especially when a "mixture" of anticancer drugs are present in a water body.…”
Section: Anticancer Drugs Toxicitysupporting
confidence: 79%
“…In general, the highest reported concentrations of antineoplastics were found in hospital effluent and WWTP influent samples, with concentrations in the ng/L to µg/L range, depending on the pharmaceutical. For example, cyclophosphamide, which was detected the most frequently across studies (Figure 1), appeared in concentrations as high as 616 µg/L in hospital effluent (Isidori et al 2016) and 13.1 µg/L in WWTP influent (Gómez‐Canela et al 2012). Other antineoplastics commonly detected in these locations were 5‐fluorouracil, ifosfamide, methotrexate, and tamoxifen, with hospital effluent concentrations as high as 122 µg/L for 5‐fluorouracil (Mahnik et al 2004), 86.2 µg/L for ifosfamide (Gómez‐Canela et al 2014), 4.7 µg/L for methotrexate (Yin et al 2010), and 0.17 µg/L for tamoxifen (Ferrando‐Climent et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is faster than HPLC and inexpensive (Mahnik et al 2004(Mahnik et al , 2007. Inductively coupled plasma mass spectrometry was used for the detection of platinum-based anticancer drugs such as cisplatin (Vidmar et al 2015;Isidori et al 2016).…”
Section: Analytical Techniquesmentioning
confidence: 99%